2018
DOI: 10.3892/ijo.2018.4651
|View full text |Cite
|
Sign up to set email alerts
|

CD38 affects the biological behavior and energy metabolism of nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) is the most common malignant tumor type in Southern China and South-East Asia. Cluster of differentiation (CD)38 is highly expressed in the human immune system and participates in the activation of T, natural killer and plasma cells mediated by CD2 and CD3 through synergistic action. CD38 is a type II transmembrane glycoprotein, which was observed to mediate diverse activities, including signal transduction, cell adhesion and cyclic ADP-ribose synthesis. However, the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…CD38 research originally focused on hematological tumors, including CLL and multiple myeloma. However, with more research expanding the field, CD38 has been confirmed as expressed in multiple types of solid tumors such as nasopharyngeal cancer ( 19 ), cervical cancer ( 20 ), and skin cutaneous melanoma ( 21 ). CD38 is a non-lineage restricted glycoprotein expressed in both non-hematopoietic cells and diverse immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 research originally focused on hematological tumors, including CLL and multiple myeloma. However, with more research expanding the field, CD38 has been confirmed as expressed in multiple types of solid tumors such as nasopharyngeal cancer ( 19 ), cervical cancer ( 20 ), and skin cutaneous melanoma ( 21 ). CD38 is a non-lineage restricted glycoprotein expressed in both non-hematopoietic cells and diverse immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 converts NAD + to ADP − ribose (ADPR) and cADPR, which are essential for regulating extracellular metabolites, intracellular Ca2 + level, cell adhesion, and signal transduction pathways [20]. CD38 inhibited the nasopharyngeal carcinoma (NPC) cells apoptosis by regulating intracellular Ca2 + concentration, ATP concentration and reactive oxygen species (ROS) signals [10]. CD38 inhibited CD8 + T-cell proliferation through producing adenosine [21].…”
Section: Discussionmentioning
confidence: 99%
“…One previous study reported that CD38 reduced tumor cell senescence and increased cell metastasis in nasopharyngeal carcinoma [10]. Moreover, Zhang, et al found that the high expression of CD38 was correlated with the poor prognosis of pancreatic ductal adenocarcinoma [11].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, tumor hypoxia recruits Treg cells in the TME via the upregulation of chemokines, while the increased expression of FasL on the tumor endothelial barrier in hypoxic conditions can selectively eliminate effector CD8 + T cells. Increased expression of ANGPT2 mRNA in mononuclear cells of untreated CLL patients has been associated with high CD38 expression [ 219 ], which influences the expression of hypoxia-inducible factor 1-alpha (HIF-1α) [ 220 ]. The overexpression of HIF-1α has been associated with poor prognosis and an aggressive phenotype in several malignant tumors [ 221 , 222 , 223 ].…”
Section: Role Of Cd38 In Hpdmentioning
confidence: 99%